2020
DOI: 10.1029/2019ja027530
|View full text |Cite
|
Sign up to set email alerts
|

The Deflection of Coronal Mass Ejections by the Ambient Coronal Magnetic Field Configuration

Abstract: Solar coronal mass ejections (CMEs) are sometimes deflected during their propagation. This deflection may be the consequence of an interaction between the CME and the ambient coronal field, for example, a coronal hole, or the solar wind. The coronal magnetic field configuration is computed from daily synoptic maps of magnetic field from SOHO/MDI and SDO/HMI using a Potential Field Source Surface model. We analyze 30 halo‐CMEs whose deflection angle exceeds 90° by comparing the ambient magnetic field configurat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 64 publications
2
10
0
Order By: Relevance
“…The CME is therefore likely to be influenced by B 2 present in the surrounding potential field, in agreement with previous studies (Gui et al 2011;Kay et al 2013;Sieyra et al 2001, and references therein) and to be deflected southward contrary to the general equatorial deflection of many CMEs (Cremades & Bothmer 2004). The presence of open field lines, deflected toward the south, is also expected to deflect the CME along them (Mäkelä et al 2013;Wang et al 2020, and references therein).…”
Section: Global Magnetic Field Modelsupporting
confidence: 88%
“…The CME is therefore likely to be influenced by B 2 present in the surrounding potential field, in agreement with previous studies (Gui et al 2011;Kay et al 2013;Sieyra et al 2001, and references therein) and to be deflected southward contrary to the general equatorial deflection of many CMEs (Cremades & Bothmer 2004). The presence of open field lines, deflected toward the south, is also expected to deflect the CME along them (Mäkelä et al 2013;Wang et al 2020, and references therein).…”
Section: Global Magnetic Field Modelsupporting
confidence: 88%
“…Moving further, we also found that the CME deflected away from radial direction, most likely after the aforesaid interaction. Such CMEs provide useful reference for space weather forecasting, especially for CME arrival and geoeffectiveness (Wang et al 2020). This suggests a possible working hypothesis for a future research, i.e.…”
Section: Discussionmentioning
confidence: 83%
“…It is generally accepted that neighboring magnetic structures, such as coronal holes (CHs -e.g., Cremades et al 2006;Gopalswamy et al 2009;Sahade et al 2020Sahade et al , 2021 and active regions (ARs -e.g., Kay et al 2015;Möstl et al 2015;Wang et al 2015), can deflect MFRs in longitude and latitude against their position. On the other hand, heliospheric current sheets (e.g., Liewer et al 2015;Wang et al 2020), helmet-streamers (e.g., Zuccarello et al 2012;Yang et al 2018), and pseudostreamers (PSs -e.g., Cécere et al 2020;Wang et al 2020;Karna et al 2021;Sahade et al 2022) attract MFRs toward their low magnetic field regions. This responses can be quantified, in strength and direction, by the local and global gradients of the magnetic pressure (Gui et al 2011;Panasenco et al 2013;Liewer et al 2015;Sieyra et al 2020).…”
Section: Introductionmentioning
confidence: 99%